Teachers’ leadership styles for learning and student academic press/emphasis: a weird relationship? - Kunalan, Hemathy; Mohd Ali, Hairuddin; Nordin, Mohamad Sahari (Readers Insight Publisher, 2018)
This study proposed to address two research hypotheses; H1: Coercive (COE) and coaching (COA) leadership styles represent the leadership styles practices of the English subject teachers at the selected national secondary schools in Kuala Lumpur, Malaysia and H2: There is a significant relationship between English subject teachers’ leadership styles practices with the students’ AP/AE in selected national secondary schools in Kuala Lumpur, Malaysia. The results showed that academic press/emphasis (AP/AE) is determined by leadership style practices particularly COA except COE. Interestingly there is strong evidence that almost all English subject teachers from all three selected schools understudy did not exhibit COE leadership style compared to COA which was the most influential predictor. They might probably try to avoid in practicing COE leadership style as this would create reinforcement patterns among the students. For this reason